The Americanization of human rights : Iranian, African, and Chinese lives in American autobiography - Klaas, Sunčica (American studies (Munich, Germany), 2018)
At least since The 'New York Times Magazine' proclaimed the triumph of the confessional narrative in 1996, the U.S. American literary market has been flooded with autobiographies by survivors of human rights violations. But why are these narratives so appealing to American readers and literary markets? Who gets to testify to victimization and survival in an autobiographical genre? What subjects are recognized as human rights personae and victims worthy of humanitarian rescue and what testimonial scripts and socio-political trajectories influence such recognitions? How is the American national community invested in these processes, and how do such autobiographies relate to the national technologies of screening, incorporating and containing potential members? The present study answers these questions by reconstructing the genealogy of the present encounter between the autobiographical and the human rights discourse and by presenting an extensive archive of contemporary autobiographies by Iranian American women, the Lost Boys of Sudan, and Tiananmen dissidents, the study focuses on the epistemic injustices produced by unequal distribution of the rights to autobiography and humanitarian rescue.